The World Bank Annual Report 2001 : Volume 2. Financial Statements and Appendixes - World Bank (Washington, DC, 2013)
This Annual Report covers the period from July 1, 2000, to June 30, 2001, and details the World Bank strategy for meeting the poverty challenge. After the Introduction, Chapter 1 provides an overview of Bank activities in 2001 that focused on multi-dimensional support, improved development effectiveness, increased funding volume, formalized the country business model, evolved country assistance strategies by preparing them in consultation, developed investment vehicles to support low-income countries, created a task force to consider the response to the needs of middle-income countries, developed an innovative IBRD and IDA program and project lending to support strong national programs, assessment of the Strategic Compact, the use of the World Bank Institute to empower through knowledge and setting out a strategic framework for future directions. Chapter 2 describes the role of the Board of Executive Directors. Chapter 3 examines the thematic issues the Bank is tackling, such as addressing the social, institutional, and economic dimensions of poverty; investing in people; supporting private sector development; building strong financial systems; and building effective legal and judicial systems. Chapter 4 discusses the Bank's role in fighting poverty and aiding development region by region. Chapter 5 looks at Bank project performance. Chapter 6 focuses on Bank partnerships, Chapter 7 sums up approved projects, and Chapter 8 provides organizational information. This report is in 2 volumes. Volume 2 comprises the complete Management's Discussion and Analysis, audited financial statements, and appendices.